2014
DOI: 10.1055/s-0034-1382488
|View full text |Cite
|
Sign up to set email alerts
|

Two new flavone glycosides from Chenopodium ambrosioides growing wildly in Egypt

Abstract: Chenopodium ambrosioides (Chenopodiaceae) growing wildly in Egypt was subjected to antioxidant-guided phytochemical investigation and the EtOAc fraction afforded the two new flavone glycosides; scutellarein-7-O-α-rhamnopyranosyl-(1→2)-α-rhamnopyranosyl-(1→2)-α-rhamnopyranoside (1) and scutellarein-7-O-α-rhamnopyranosyl-(1→2)-α-rhamnopyranoside (2). In addition, the in vitro antioxidant activities of the plant alcohol extract, CHCl 3 fraction, EtOAc fraction and isolates were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Reviewing the literature revealed that the different parts of C. ambrosioides showed numerous biological activities i.e., antimicrobial 16,17 , cytotoxicity 18 , antioxidant 19 , larvicidal 20 , antidiabetic 4 , antiparasitic 21 , antiviral 22 , and molluscidal 23 . Moreover, from the phytochemistry point of view C. ambrosioides is known to contain secondary metabolites i.e., saponins 24 , terpenoids 2,25,26 , flavonol glycosides 27,28 , flavone glycosides 29 , and chenopodiumamines & chenopodiumoside 30 . The accumulation of the reactive free radicals in our bodies led to phenomena known as oxidative stress which represent the imbalance between the endogenous antioxidant molecules in our bodies and the extent of such species.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature revealed that the different parts of C. ambrosioides showed numerous biological activities i.e., antimicrobial 16,17 , cytotoxicity 18 , antioxidant 19 , larvicidal 20 , antidiabetic 4 , antiparasitic 21 , antiviral 22 , and molluscidal 23 . Moreover, from the phytochemistry point of view C. ambrosioides is known to contain secondary metabolites i.e., saponins 24 , terpenoids 2,25,26 , flavonol glycosides 27,28 , flavone glycosides 29 , and chenopodiumamines & chenopodiumoside 30 . The accumulation of the reactive free radicals in our bodies led to phenomena known as oxidative stress which represent the imbalance between the endogenous antioxidant molecules in our bodies and the extent of such species.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism in various species of Chenopodiaceae is known to synthesize mainly glycosides of quercetin, kaempferol and isorhamnetin. The carbohydrates that are involved in the structure of glycosides are glucose, galactose, rhamnose and apiose [ 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%